2020
DOI: 10.1002/cyto.a.24188
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Non‐Classical and Intermediate Monocyte Subsets in Severe Acute SARS‐CoV‐2 Infection

Abstract: In patients with severe SARS‐CoV‐2 infection, the development of cytokine storm induces extensive lung damage, and monocytes play a role in this pathological process. Non‐classical (NC) and intermediate (INT) monocytes are known to be involved during viral and bacterial infections. In this study, 30 patients with different manifestations of acute SARS‐CoV‐2 infection were investigated with a flow cytometric study of NC, INT, and classical (CL) monocytes. Significantly reduced NC and INT monocytes and a downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
72
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 10 publications
23
72
1
1
Order By: Relevance
“…The MVS is predominantly expressed in the myeloid cells. First, we found the MVS increased at a single-cell level in CD14+ monocytes, which increase with the severity of viral infection, whereas CD16+ monocytes decrease, which is in line with several recent studies of patients infected with SARS-CoV-2 (Gatti et al, 2020;Hadjadj et al, 2020;Silvin et al, 2020;Zhou et al, 2020). This suggests that reduced CD16+ monocytes in peripheral blood, possibly due to efflux to the site of infection in response to ongoing tissue damage or dysregulated cytokine sensing, is a conserved feature of the host response in severe viral infection across viruses, and may have prognostic significance.…”
Section: Discussionsupporting
confidence: 92%
“…The MVS is predominantly expressed in the myeloid cells. First, we found the MVS increased at a single-cell level in CD14+ monocytes, which increase with the severity of viral infection, whereas CD16+ monocytes decrease, which is in line with several recent studies of patients infected with SARS-CoV-2 (Gatti et al, 2020;Hadjadj et al, 2020;Silvin et al, 2020;Zhou et al, 2020). This suggests that reduced CD16+ monocytes in peripheral blood, possibly due to efflux to the site of infection in response to ongoing tissue damage or dysregulated cytokine sensing, is a conserved feature of the host response in severe viral infection across viruses, and may have prognostic significance.…”
Section: Discussionsupporting
confidence: 92%
“…While the elevated CCR2 on ncMonos found here may present an explanation for their more pronounced disappearance from the circulation in severe COVID-19, a sequential transition model might also explain the decrease of ncMonos detected in COVID-19 patients by us (Fig. 4C, D) and others 20,27,35,42 .…”
Section: Independent Assessment Of the Mnp Landscape Identifies Clinisupporting
confidence: 52%
“…In vivo acute inflammatory response, induced by the virus, and the subsequent cytokine release stimulates the up-regulation of CD11b/CD18 that favors thrombosis. We know that the role of anti IL6 drugs on the regulation of the expression of CD11bCD/18 on monocytes macrophages was previously studied in inflammation in atherosclerosis and in myocardial ischemia; our data, even in light of our recent work [ 6 ], and once completed, could help to demonstrate the hypothesis that the interaction between CD11b/CD18, endothelial cells platelets, factor X and fibrinogen plays a fundamental role in favoring inflammation and thrombosis. The overproduction of early response proinflammatory results in what has been described as an inflammatory storm, leading to an increased risk of vascular hyperpermeability, multiorgan failure, and death.…”
mentioning
confidence: 57%
“…Our recent work [ 6 ] showed that, during the monitoring of patients infected by SARS-CoV-2 a reproducible decrease of peripheral Non-classical (NC) and intermediate (INT) monocyte was found in subjects with the most severe clinical status at admission suggesting that their decreasing may be considered prognostic indicators that may help in the early identification of patients with the worst and most rapid unfavorable outcome.…”
mentioning
confidence: 99%